Strategi Human Resource dalam Mengelola “Quiet Quitting” di Kalangan Karyawan Milenial: Studi Kasus di Startup Digital - Burhanuddin, Burhanuddin (PT Maju Malaqbi Makkarana, 2025)
This study examines human resource (HR) strategies in managing the phenomenon of quiet quitting among millennial employees in Jakarta's digital startups. Using a qualitative case study approach, data were collected through in-depth interviews with 15 millennial employees, 5 HR managers, 2 startup founders, and analysis of policy documents. Findings reveal that quiet quitting stems from an imbalance between high job demands (hustle culture) and insufficient psychological support, including a lack of recognition and one-way feedback systems. Effective HR strategies involve flexible policies (hybrid work, job crafting), well-being programs, and cultural adaptation based on local collectivist values. The study underscores the importance of human-centered HR approaches that integrate global flexibility with sensitivity to Jakarta’s socio-cultural context. Practical implications recommend integrating mental well-being indicators into performance evaluations and fostering multi-stakeholder collaboration to build a sustainable work ecosystem.